File security on cloud using hybrid encryption - Gupta, Reema (My University, 2013)
Cloud computing is next generation architecture of IT Enterprise. In contrast to traditional solutions, Cloud computing moves the application software and files to the large data centers, where the management of the files and services may not be fully trustworthy. This unique feature, however, raises many new security challenges which have not been well understood. The resources of Cloud are shared among all of the servers, users and individuals. As such, it is difficult for the cloud provider to ensure file security. As a result, it is very easy for an intruder to access, misuse and destroy the original form of data. In case of compromise at any cost; entrusting cloud is of no use. There is need to have “practically infeasible to attack” solution for file information preserving system on cloud. The proposed approach uses hybrid ryptosystem. If the data stored in the cloud is in encrypted form, it would effectively solve various security issues. The proposed hybrid cryptosystem uses a combination of Blowfish Algorithm coupled with file splitting and merging mechanism and SRNN Algorithm. The performance of symmetric algorithm is integrated with security of asymmetric algorithm.
Master of Technology, Computer Application, Dissertation
Keywords: File Security; Cloud; Hybrid Encryption